Root Tensile Characteristics of Herbaceous Plants from Source Areas of Lanniqing Landslide in Zhaotong City, Yunnan Province - Xu Zongheng; Chen Yunying; Zhang Yu; Zha Linglong; Tao Zhenpeng (Shuitu baochi tongbao)
[Objective] The tensile strength characteristics of plant roots were studied to understand the performance of roots in complexes, in order to provide a basis for the selection of plants to be used in ecological slope protection. [Methods] Single root tensile tests were carried out on the roots of Iris tectorummaxim and Artemisia argyi taken from the source areas of the Lanniqing Landslide in Zhaotong City, Yunnan Province. The deformation and failure characteristics and tensile strength features were determined from macroscopic failure characteristics, deformation-tension curve, and feature parameters of fracture tension, maximum tension force, tensile strength, elongation rate, and tensile modulus. [Results] ① Iris root damage showed obvious ductility, while A. argyi root damage showed brittleness. The average elongation rate of I. tectorummaxim was about three times of A. argyi when damaged, and the root system of I. tectorummaxim showed good elastic-plastic deformation characteristics and strong deformation ability in the tensile process. ② Due to the protective effect of the periderm, the deformation-tension curves of Iris tectorummaxim roots mostly showed fluctuation and multiple peak values, while the roots of A. argyi mainly showed an approximately linear response. ③ Diameter and length significantly affected the mechanical features and parameters of roots. Fracture tension and maximum tension force increased with increasing root diameter, while tensile strength and tensile modulus decreased. The variation of the characteristic parameters of tensile strength was enhanced when the root length was short. Therefore, it is recommended that plants be selected that have little change in root diameter along the axial direction and the roots be as long as possible when carrying out relevant mechanical tests. [Conclusion] We recommend selecting vegetation with good root tissue structure, thick periderm tissue, strong deformation ability, large elongation rate, and obvious ductile failure characteristics to be used as slope protection plants.